Perbandingan Kesiapan Belajar Mahasiswa Lulusan Sekolah Umum Dan Berbasis Islam Pada Program Studi Pendidikan Agama Islam Fakultas Tarbiyah Dan Ilmu Keguruan Universitas Islam Negeri Datokarama Palu - Rahim, Muspaida; Rusdin, Rusdin; Rus’an, Rus’an (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2025)
This study discusses the comparison of learning readiness of students who graduated from public and Islamic-based schools in the Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training, UIN Datokarama Palu. The problem raised in this study is whether there is a difference in learning readiness of students who graduated from public and Islamic-based schools in the Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training, UIN Datokarama Palu. This study uses a quantitative approach with a comparative research design. The population of this study consisted of students of the 2024 batch of the Islamic Religious Education Study Program at UIN Datokarama Palu. Data were collected through questionnaires or surveys that measured students' learning readiness, with data analysis using descriptive statistics and inferential statistics. The results of the study showed that the average learning readiness score of students who graduated from public schools was 73.26. While students who graduated from Islamic-based schools had an average of 73.97. The results of the inferential statistical analysis through the Independent Sample t-test produced a sig value (2-tailed) of 0.663, which was greater than the probability value of 0.05. Based on the decision of the Independent Sample t-test, Ho is accepted and Ha is rejected, which means there is no significant difference in learning readiness between students who graduated from public schools and Islamic-based schools in the Islamic Religious Education Study Program, Faculty of Tarbiyah and Teacher Training, UIN Datokarama Palu. The implication of this study is that students can improve their learning readiness so that the objectives of learning can be achieved optimally